Cellular Features Revealed by Transverse Laser Modes in Frequency Domain. Issue 1 (28th November 2021) - Qiao, Zhen; Xu, Hongmei; Zhang, Na; Gong, Xuerui; Gong, Chaoyang; Yang, Guang; Chew, Sing Yian; Huang, Changjin; Chen, Yu‐Cheng
Abstract: Biological lasers which utilize Fabry–Pérot (FP) cavities have attracted tremendous interest due to their potential in amplifying subtle biological changes. Transverse laser modes generated from cells serve as distinct fingerprints of individual cells; however, most lasing signals lack the ability to provide key information about the cell due to high complexity of transverse modes. The missing key, therefore, hinders it from practical applications in biomedicine. This study reveals the key mechanism governing the frequency distributions of transverse modes in cellular lasers. Spatial information of cells including curvature can be interpreted through spectral information of transverse modes by means of hyperspectral imaging. Theoretical studies are conducted to explore the correlation between the cross‐sectional morphology of a cell and lasing frequencies of transverse modes. Experimentally, the spectral characteristics of transverse modes are investigated in live and fixed cells with different morphological features. By extracting laser modes in frequency domain, the proposed concept is applied for studying cell adhesion process and cell classification from rat cortices. This study expands a new analytical dimension of cell lasers, opening an avenue for subcellular analysis in biophotonic applications. Abstract : This study reveals the key mechanism governing the frequency distributions of transverse modes in single cell biological lasers. Morphological information of cells can be interpreted through hyperspectral imaging of laser modes. Applications including cell classification and monitoring of cell adhesion are explored and demonstrated.